The effectiveness of rhythmic movement games training on separation anxiety in children - Faramarzi , Salar; Bakrayi , Saadi; Mohebzadeh , Majid; Aghaziarati, Ali; Ranjbar , Badr (Applied Family Therapy Journal (AFTJ), 2020)
Aim: This study aimed to determine the effectiveness of rhythmic movement game training on reducing separation anxiety in children aged 5 to 6 years. Method: Quasi-experimental research method with pre-test-post-test design with a control group and two-month follow-up and the population studied in this study were 29 children aged 5 to 6 years with separation anxiety referred to the specialized family and child clinic of Shahid Beheshti University in 2018. After screening with the Separation Anxiety Scale of Hahn, Hajinlian, Eisen, Winder, and Pincus (2003) 24 children were selected purposefully and randomly assigned to experimental and control groups (12 children in each group). The experimental group underwent the Rafie Rhythmic Movement Games training package for 8 sessions (2012), but the control group did not receive any intervention. Data were analyzed using a mixed analysis of variance. Results: The results showed that rhythmic movement game training affects the total score of separation anxiety (F = 10.60, P = 0.004), fear of being alone (F = 7.43, P = 0.012), fear of abandonment. (F = 10.31, P = 0.004), fear of physical illness (F = 10.09, P = 0.004) and worry about calamitous events (F = 3.97, P = 0.049). And this effect was sustained in the follow-up phase. Conclusion: Teaching rhythmic movement games is an effective strategic intervention to reduce separation anxiety in children. Based on the results of this study, child counselors and psychologists can be suggested to use this treatment to try to reduce separation anxiety in children.